(untitled) (Bangladesh Journal of Botany, 2023)
Soybean (Glycine max L. Merr.) is one of the most important crops worldwide providing valuable nutrients and proteins. Previously, disease resistance against Psuedomonas putida infection was induced in soybean sprouts germinated under red right irradiation at 660 nm wavelength. Microarray analysis was conducted to elucidate the underlying molecular mechanisms contributing to this red-light-induced disease resistance. Four different treatments were carried out: (1) incubation in darkness without pathogen inoculation (DN), (2) incubation in darkness followed by pathogen inoculation (DI), (3) incubation under red light without pathogen inoculation (RN), and (4) incubation under red light followed by pathogen inoculation (RI). Four different comparisons were made between gene expression sets as follows: (1) DI vs. DN (DI/DN), (2) RI vs. RN (RI/RN), (3) RI vs. DI (RI/DI), and (4) RN vs. DN (RN/DN). Genes exhibiting 3-fold up- or down-regulated changes in expression were scored, which revealed 1539 and 1301 up-regulated and down-regulated genes, respectively. For the comparisons between gene expression sets DI/DN, RI/RN, RI/DI, and RN/DN, there were 1078, 651, 68, and 71 differentially regulated genes, respectively. These genes were further characterized according to their biological processes and molecular functions, and gene expression changes indicated by microarray analysis were validated by real-time PCR. Red-light irradiation regulates expression changes in many genes, whose profiles should be identified to elucidate the complex processes underlying the induced disease resistance. Bangladesh J. Bot. 52(1): 129-139, 2023 (March)